LEGAL PROTECTION FOR THE OBLIGEE CAUSED BY FAKE PERFORMANCE BONDS (LEGAL CONSTRUCTION TO DISPUTE SETTLEMENT IN CONSTRUCTION LAW) - Octaviani Cristiani Purnama Sari (Legal Standing : Jurnal Ilmu Hukum, 2018)
In a development project activity, financing is a very significant thing. Therefore, in all its activities required a smooth transaction in terms of financing, because without it will certainly be many obstacles that will be experienced by the owners of the project. To avoid this, project owners often involve third parties to ensure liquidity of funds. In order to guarantee this, project owners often use the services of banking institutions. The provisions contained in Law No. 2 of 2017 concerning Construction Services (hereinafter referred to as Construction Services Law) in Article 57 paragraph (1) provides that: "In selection of service providers as referred to in Article 42, the service provider shall submit a guarantee to the Service User to fulfill the obligations as required in the Service Provider's selection document ". Guarantees referred to by the above article is nothing but the guarantee of the implementation of the bank guarantee (performance bond) .But in reality often found bank warranty issuance turned out to be fake and cause dispute.